Low Genetic Diversity Study on Leopard Coral Grouper Plectropomus leopardus (Perciformes: Serranidae) from Sulawesi, Indonesia - Andi Aliah Hidayani; Asmi Citra Malina A. R. Tasakka; Widyastuti Umar; Md. Jobaidul Alam; Amit Kumer Neogi; Sapto Andriyono (Faculty of Fisheries and Marine Universitas Airlangga, 2022)
Highlight ResearchThe leopard coral grouper Plectropomus leopardus was identified and analysed based on molecular approach.Genetic diversity within two regions in Gorontalo, Sulawesi successfully performed using connectivity analysis.Three haplotypes of Plectropomus leopardus from two region in Gorontalo as one of economical important marine fish species. AbstractBar-cheek coral trout (P. leopardus) is the flagship of the grouper in the live fish market in Asia. Unfortunately, the potential of the grouper is still partly produced from natural catches. Even though hybridisation activities have also started to be carried out, there still have not been many studies on the genetic diversity of these fish. The application of molecular identification has been widely applied in marine aquatic animal species, which are very likely to occur due to errors in terms of shape and colour in the morphological character. DNA information has been beneficial in efforts to the breeding program and develop grouper aquaculture activities. DNA barcoding was used for the molecular identification and haplotype analysis of P. leopardus from two locations in Gorontalo, Sulawesi, Indonesia. A total of 14 fish samples were collected from two traditional fish markets around Kwandang and Sumalata Gulf in the northern part of Gorontalo Province, Sulawesi. This study identified and found three haplotypes from both regions. Molecular identification using Cytochrome c Oxidase subunit I (COI) gene region on mitochondrial DNA. Besides Mega7 for phylogenetic reconstruction, the data analysis using DnaSP6, Arlequin Ver.3.5.2.2, and Network 5.0.1.1. The first Haplotype is a mixed population between the Kwandang Gulf and the Sumalata Gulf, then the Kwandang Gulf haplotype and the Sumalata Gulf haplotype. The genetic distance between Kwandang Gulf haplotype and Sumalata Gulf haplotype is 0.003984, classified as a shallow genetic distance and needs more samples from another region to figure out leopard coral grouper around Indonesia.